2014
DOI: 10.1371/journal.pntd.0003093
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of (-)-Epigallocatechin 3-O - Gallate In Vitro and In Vivo in Leishmania braziliensis: Involvement of Reactive Oxygen Species as a Mechanism of Action

Abstract: BackgroundLeishmaniasis is a parasitic disease associated with extensive mortality and morbidity. The treatment for leishmaniasis is currently based on pentavalent antimonials and amphotericin B; however, these drugs result in numerous adverse side effects. Natural compounds have been used as novel treatments for parasitic diseases. In this paper, we evaluated the effect of (-)-epigallocatechin 3-O-gallate (EGCG) on Leishmania braziliensis in vitro and in vivo and described the mechanism of EGCG action against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 55 publications
(67 reference statements)
3
51
0
1
Order By: Relevance
“…[10][11][12]20 Treatment with 1 for 24 h increased ROS generation in L. amazonensis in a concentration-dependent manner (p < 0.01) ( Figure 2). ROS levels in L. amazonensis treated with 1 (96 μM) were 2.9-fold higher than those of the control.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…[10][11][12]20 Treatment with 1 for 24 h increased ROS generation in L. amazonensis in a concentration-dependent manner (p < 0.01) ( Figure 2). ROS levels in L. amazonensis treated with 1 (96 μM) were 2.9-fold higher than those of the control.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The compound enhanced the production of radicals, both ROS and RNS (Jeong, Park, Cho et al, 2015). A study was made of the drug effect on Leishmania (Inacio, Gervazoni, Canto-Cavalheiro et al, 2014). Results suggest a mode of action involving ROS.…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
“…19,20 A recent study suggested that biological compounds that involve the production of reactive oxygen species (ROS) may induce cell death in various leishmaniasis. 21,22 Almeida-Amaral and co-workers reported that the flavonol quercetin and the epigallocatechin gallate (Scheme 1. ), known potent antioxidants, induced death in Leishamania amazonensis and braziliensis respectively.…”
mentioning
confidence: 99%
“…), known potent antioxidants, induced death in Leishamania amazonensis and braziliensis respectively. 21,22 Recently, Stockwell and co-workers reported the discovery of an arylalkylamine AA1-type compound (Fer-1) that was shown to be a potent and specific inhibitor of a unique form of non-apoptoptic, iron-dependent, oxidative cell death, known as ferroptosis. 23,24 The Fer-1 compound inhibits the lipid ROS production through an anti-oxidant mechanism.…”
mentioning
confidence: 99%
See 1 more Smart Citation